(untitled) (Journal of the College of Education for Women, 2019)
In his post colonial novel, In the Skin of a lion, the Canadian/Sri Lankan writer,Michael Ondaatje is so interested in the term "Post colonialism" because he wants to showthat the term doesn’t only refer to a period of time that comes after colonialism. In otherwords, post colonialism is not only referred to as a literal description of formerly colonialsocieties. He deals with the termas a literary genre and an academic construct that describesthe global conditions of a man after a period of colonialism. He shows that post colonialism isa theory that tries to examine and explore the different styles and faces of European authorityto control the colonized. Ondaatje’s attempt through such term is to unmask Europeanauthority and to focus on those who are excluded such as the immigrants and the outsiderswho feel lost and without identities in their world. Thus, he writes In the Skin of a Lion toretell and illuminate the story of the marginalized characters of Toronto who are used andcontrolled by the colonizers to build Toronto but they remained as outsiders. The writer triesto weave the story around such characters as Caravaggio the thief, Nicholas Temelcoff thedaredevil, Patrick the tunnel worker, and Alice the nun to show how the colonial powersdominated over them, marginalized and alienated them in a city where they sought home. Heshows how the barriers of language, culture and beliefs hold these individuals back andimprison them in "the tunnels and the stockyards". They were denied even the right tocommunicate in their own language. This is because of the " rule of the city", a city thatimposes on them their philosophies and values on struggling. It made them known only bytheir trade, "A starrer of roads, a house builder, a painter, a thief". Ondaatje resorts to TheEpic of Gilgamesh to suggest thematically the title of his novel as In the Skin of a Lion. Heemphasizes the idea of assuming the skin of a lion to take action because each one hasresponsibility in life. To sum up, the novel is a call to provide the opportunity for the oncemarginalized persons to stand and to be heard. In other words, the novel is about thetransformation of identities in the shed of the colonialism.